Organização do trabalho pedagógico na educação infantil: um olhar sobre a rotina com as crianças de zero a dois anos - Bezerra, Dayanna Cristine Gomes Rosa (2019)
The presented research is characterized as a subproject linked to the research project developed by the Center for Studies and Research on Childhood and its Education in Different Contexts called Public Policies and Early Childhood Education in Goiás: stories, conceptions, projects. and practices. This project is linked to the research line Teacher Education, Teacher Professionalization and Educational Work of the Graduate Program in Education of the Faculty of Education of the Federal University of Goiás. We investigated what were the dimensions that made up the organization of the pedagogical work and which of them were considered by the preschool teachers in the planning and routine execution with children from zero to two years, in view of the specificities in this phase of development. The qualitative research, having as theoretical assumption the historical-dialectical materialism, was developed through the case study, using different research methodologies, such as reading and analysis of documents; observation and recording in the field diary; questionnaire and interview. Thus, it can be understood that the organization of pedagogical work is based on a pedagogical proposal, as it contemplates different conceptions that permeate the institution's daily life, reflecting on the teaching performance. Routine is one of the dimensions that constitute the pedagogical work organization, since it is not isolated from other aspects of work. The analysis of the research data indicated the following research categories: 1) routine and daily life; 2) articulation of caring and educating; 3) child conception and teaching work; and 4) structure and working conditions. The whole analyzes considered the pedagogical work developed with children under two years, as well as the specificity of the children care in this age group. Thereby, the defense was made by a routine conception as continuous actions developed with the children, systematically and intentionally, as a way to organize the actions of the environment and projects, considering the conception of children; the learning and development process; the articulation of caring and educating, as well as the role of the preschool teacher, having as reference the objectives of this stage of education, in addition to other dimensions that make up the organization of the pedagogical work.